Understanding the needs of professionals who provide psychosocial care for children and adults with disorders of sex development. Issue 1 (31st August 2017) - Dessens, Arianne; Guaragna-Filho, Guilherme; Kyriakou, Andreas; Bryce, Jillian; Sanders, Caroline; Nordenskjöld, Agneta; Rozas, Marta; Iotova, Violeta; Ediati, Annastasia; Juul, Anders; Krawczynski, Maciej; Hiort, Olaf; et al.
Abstract : Objective: Disorders in sex development (DSD) can be treated well medically, but families will encounter many psychosocial challenges. Promoting counselling to facilitate acceptance and coping is important yet equality of access is unknown. This study investigated the modalities of psychosocial care provided in centres of DSD care. Methods: An international survey conducted among 93 providers of psychosocial care, identified through clinical networks, registries and professional forums. Results: Forty-six respondents from 22 different countries filled out the survey (49%). Most respondents (78%) were based in hospital-based expert teams. Referrals came from paediatric endocrinologists (76%), gynaecologists (39%) and paediatric urologists (37%). Psychological counselling was most frequently given to parents (74%), followed by children (39%), adolescents (37%) and adults (11%) and was most frequently focused on coping and acceptance of DSD (54%), education (52%), the atypical body (39%) and genital (41%), decisions on genital surgery (33%), complications with sexual intercourse (29%), disclosure (28%) and acceptance of infertility (11%). Respondents most frequently observed DSD related confusion about gender (54%), acceptance of cross gender behaviour (50%), anxiety (43%) and sadness and depression (38%). Conclusions: Most psychosocial care is provided to parents. It is assumed that parental support is important as acceptance is conditional to become affectionate caretakers. Although it may be more difficult for youngsters to communicate about their condition and treatment, providing opportunity to bring up issues that are important for them, is imperative. Clinicians and parents should be aware that parental and patients' interests may not correspond completely. Psychosocial management should also include transition and adult care.